Rancang Bangun Game Edukasi Matematika Bilangan Pecahan sebagai Media Pembelajaran untuk Siswa SDN 14 Sungai Raya - Musyriyah, Musyriyah; Maulana, Adha; Awanis (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Mathematics is a science obtained by reasoning which uses definitional terms carefully, clearly and accurately. Mathematics is a compulsory subject at every level of education from elementary school. So far, mathematics is a subject that is less popular with students at SDN 14 Sungai Raya school. Some things that cause mathematics lessons to be considered difficult by students are because mathematics lessons use too many formulas. Some students who feel that they are unable to understand what the teacher is saying decrease their interest in learning. Along with technological developments, a simple application in the form of a game is used as a medium for learning fractional mathematics which is created using Construct 3, an HTML5-based 2D Game engine, Construct 3 can be run via the Chrome Browser. The design method used in this research is RAD (Rapid Application Development). One method of system development strategy that prioritizes development speed through broad user involvement in the use of a series of constructions. The results of this research are that the fractional math educational game application can run well. The material presented can help students in learning. Based on tests on students, the application as a whole has received a good response with a percentage of 81%, so it can be concluded that this application can be used as a learning medium at SDN 14 Sungai Raya.